Inhibition of Circ-Snrk ameliorates apoptosis and inflammation in acute kidney injury by regulating the MAPK pathway - Fanhang Meng; Qiuyuan Chen; Shijie Gu; Ruiwen Cui; Qing Ma; Ronghua Cao; Ming Zhao (Renal Failure, 2022)
Background Circular RNA (circRNA) is involved in the process of acute kidney injury (AKI), but only a few circRNAs have been reported. In the study, we investigated a new circRNA and its association with AKI.Methods An AKI model was established in Sprague-Dawley rats, followed by serum creatinine and urea nitrogen tests measured by a biochemical analyzer. The pathological changes and apoptosis in the renal tissue were detected by Hematoxylin and Eosin, and TUNEL staining. Then, circRNA expression in AKI was determined by quantitative real-time-PCR (qRT-PCR). NRK-52E cells were induced with hypoxia/reoxygenation (H/R) as in vitro models and the circ-Snrk level was tested by qRT-PCR. The effects of circ-Snrk in H/R-induced NRK-52E cells were assessed by flow cytometry, western blot, and enzyme-linked immunosorbent assay. Finally, RNA sequencing and western blot analysis were used to validate the mRNA profile and pathways involved in circ-Snrk knockdown in H/R-induced NRK-52E.Results A reliable AKI rat model and H/R cell model were established. qRT-PCR demonstrated that circ-Snrk level was upregulated in AKI left kidney tissue and NRK-52E cells with H/R treatment. Circ-Snrk knockdown inhibited apoptosis of NRK-52E cells and secretion of inflammatory factors (IL-6 and TNF-α). RNA sequencing showed that the mRNA profile changed after inhibition of circ-Snrk and differential expression of mRNA mainly enriched various signaling pathways, including MAPK signaling pathway. Furthermore, western blot indicated that circ-Snrk knockdown could inhibit the activation of p-JNK and p-38 transcription factors.Conclusions Circ-Snrk is involved in AKI development and associated with the MAPK signaling pathway in AKI.